China's Neoliberal Authoritarian Social Policy - Frazier, Mark W (Social research, 2024)
China is commonly regarded as a successful alternative to neoliberal economic policy and development strategy. But China's social policies, which were adopted at a pivotal global moment of postsocialist transition in the 1990s, bear significant traits one would associate with neoliberal economic policy. This article uses the case of old age pensions to support this claim. Pension reforms of the early 2000s transferred unprecedented costs and risks to Chinese households under a new social insurance scheme. Twenty years later, the inherent flaws in financing healthcare and pensions through employer-financed and individualized social insurance have become apparent. The concluding section discusses Xi Jinping's dominance of Chinese politics and the risks and economic insecurities that have afflicted Chinese society under these neoliberal social policies.